Synthesis and Crystal Structure of New Nitrogen Heterocyclic Compound - Chai*, Lan-Qin; Huang, Jiao-Jiao; Li, Yao-Xin; Zhang, Jian-Yu (Asian Journal of Chemistry, 2014)
An unexpected nitrogen heterocyclic compound has been synthesized originally. Furthermore, the compound was characterized by elemental analysis. The crystal structure of the title compound has been determined by single-crystal X-ray diffraction. It crystallizes in the orthorhombic space group Pmcn with a = 12.056(2) Å, b = 4.6016(8) Å, c = 22.185(6) Å, b = 90.00°, Z = 4. There are two fairly strong intramolecular C3-H3···N1 and C5-H5···N2 hydrogen bonds.